2016
DOI: 10.3109/10826084.2016.1156701
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Cannabis-Related Impairment: The Synergistic Influences of Peer and Parent Descriptive and Injunctive Normative Perceptions

Abstract: Objectives Cannabis users, especially socially anxious cannabis users, are influenced by perceptions of other’s use. The present study tested whether social anxiety interacted with perceptions about peer and parent beliefs to predict cannabis-related problems. Methods Participants were 148 (36.5% female, 60.1% non-Hispanic Caucasian) current cannabis users aged 18–36 (M = 21.01, SD = 3.09) who completed measures of perceived descriptive and injunctive norms, social anxiety, and cannabis use behaviors. Hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(72 reference statements)
0
5
1
Order By: Relevance
“…In our sample, psychiatric history was associated with more frequent and heavier cannabis use in the prior 90 days, but unlike other studies 27,43,44 , not with earlier onset of use or more symptoms of a cannabis use disorder.…”
Section: Discussioncontrasting
confidence: 91%
“…In our sample, psychiatric history was associated with more frequent and heavier cannabis use in the prior 90 days, but unlike other studies 27,43,44 , not with earlier onset of use or more symptoms of a cannabis use disorder.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, the results of Mahomey et al, 23 in line with the results of the current study, show that there is no significant relationship between the duration of addiction and quality of sleep. In order to explain this finding of the study, it can be said that according to previous studies, 24,25 before starting to abuse substance, addicts have a low quality of life and numerous mood and anxiety complications. Believing that substance abuse can be one of the strategies to cope with and mitigate problems, 26 these individuals tend to start abusing substance, and they want to mitigate their sleep disturbances through abusing substance, especially opiates.…”
Section: Discussionmentioning
confidence: 85%
“…Studies also reported associations with specific types of anxiety, as well as potential mediators and moderators. Generalized and social anxiety were both associated with cannabis-related problems (but not use) [50][51][52], with social anxiety also being associated with more problem severity [53] and generalized anxiety associated with use frequency (as opposed to endorsement of any use) [50,54]. Cannabis users were also more likely to endorse higher separation anxiety in adolescence compared to non-users [55].…”
Section: Primary Outcomesmentioning
confidence: 98%